Academic hardiness and its relationship to test anxiety among postgraduate students at Saudi Universities - Alharbi, S.; Alalwani, S. (South African Journal of Higher Education, 2026)
This study aimed to identify academic hardiness and its relationship to test anxiety among postgraduate students at Saudi universities. The descriptive correlation method was used to reveal the objective of the study. The study sample consisted of 541 male and female postgraduate students at Saudi universities, including 166 male and 375 female students, who were chosen using the random method. The Academic Hardiness Scale and the Test Anxiety Scale were administered after verifying the apparent and constructive validity of the two scales. The results showed that the level of academic hardiness was average with an arithmetic mean of 2.76. Test anxiety overall was averaged with an arithmetic mean of 2.39, and the values of the arithmetic mean for the dimensions ranged between 2.44‒2.29, all of which were at the intermediate level. This indicated that there were no statistically significant differences at the significance level (α = 0.05) between the arithmetic means of all sub-dimensions. For academic hardiness due to the gender variable, there were statistically significant differences between the arithmetic means of the dimensions of test anxiety in favour of females. There were positive direct correlations with statistical significance between the dimensions of academic hardiness. Test anxiety values ranged between 0.177-0.586, and academic hardiness was associated with test anxiety with a positive (direct) relationship with statistical significance with a value of 0.430. The researchers recommend conducting studies related to test anxiety for undergraduate students and linking these to the variable of specialisation to see if there is a difference between science and humanity disciplines regarding test anxiety.